Promoting Shared Prosperity in South Asia - Ghani, Ejaz; Iyer, Lakshmi; Mishra, Saurabh (World Bank, Washington, DC, 2014)
The geography of poverty has changed. More than 70 percent of the world s poor live not in low-income countries, but in middle-income countries. In 2008, nearly 570 million people lived on less than US$1.25 a day in South Asia, compared to 385 million in sub-Saharan Africa. In addition, nearly 70 percent of the poor people in South Asia live in the lagging regions. Improving the living standards of these regions is crucial to achieving the goal of shared prosperity. Economic growth is not sufficient to enable the lagging regions of South Asia to catch up with the leading regions, in terms of proportional reductions in poverty rates. Policies must be specifically targeted toward achieving greater growth and poverty reduction in these regions. One particular policy channel to achieve shared prosperity is pro-poor fiscal transfers. For the most part, interstate fiscal transfers in South Asian countries do promote equity through transfer of resources to poorer regions, but this outcome usually occurs when pro-poor redistribution has explicit rules and transparency. Further, simply directing financial resources to lagging regions may not be sufficient, and may need to be complemented with increases in capacity, transparency, and participation to facilitate accountability at the local level. Policy makers need to boost shared prosperity and take another look at the millennium development goal paradigm. A new lens is needed- one that shifts the focus of policy from national to subnational level, and from leading to lagging regions, where poverty, gender disparity, and human misery are concentrated.